Corporate Social Responsibility, Bank Efficiency, Capital and Bank Risk: Empirical Evidence of Sharia Banks in Indonesia - Haryanto, Sugeng; Aristanto, Eko; Umar Ariefudin, Muhammad; Ridloah, Siti; Bachtiar, Yanuar (Universitas Negeri Semarang, 2025)
Risk is part of the business. This study aims to determine the effect of CSR, efficiency, and capital on financing risk in Sharia banks in Indonesia. This research was conducted at Islamic banks in Indonesia. This research was conducted from 2015 to 2023. The data used in this study are secondary data sourced from annual reports published by theFinancial Services Authority (OJK) and the official websites of each Islamic bank. The data analysis method in this study is multiple linear regression analysis with panel data. Based on the research results, CSR positively affects financing risk. Efficiency can reduce financing risk. CAR has no impact on financing risk. The research variables used are still limited, so further research can be done by examining how Islamic banks manage financing.